Mesenchymal Stem Cells Therapy Improved the Streptozotocin-Induced Behavioral and Hippocampal Impairment in Rats - Zappa Villar, María Florencia (2019)
Sporadic Alzheimer’s disease (sAD) is the most prevalent neurodegenerative pathology with no effective therapy until date. This disease promotes hippocampal degeneration, which in turn affects multiple cognitive domains and daily life activities. In this study, we hypothesized that long-lasting therapy with mesenchymal stem cells (MSC) would have a restorative effect on the behavioral alterations and cognitive decline typical of sAD, as they have shown neurogenic and immunomodulatory activities. To test this, we chronically injected intravenous human MSC in a sAD rat model induced by the intracerebroventricular injection of streptozotocin (STZ). During the last 2 weeks, we performed open field, Barnes maze, and marble burying tests. STZ-treated rats displayed a poor performance in all behavioral tests. Cell therapy increased exploratory behavior, decreased anxiety, and improved spatial memory and marble burying behavior, the latter being representative of daily life activities. On the hippocampus, we found that STZ promotes neuronal loss in the Cornus Ammoni (CA1) field and decreased neurogenesis in the dentate gyrus. Also, STZ induced a reduction in hippocampal volume and presynaptic protein levels and an exacerbated microgliosis, relevant AD features. The therapy rescued CA1 neurodegeneration but did not reverse the decrease of immature neurons, suggesting that the therapy effect varied among hippocampal neuronal populations. Importantly, cell therapy ameliorated microgliosis and restored hippocampal atrophy and some presynaptic protein levels in the sAD model. These findings, by showing that intravenous injection of human MSC restores behavioral and hippocampal alterations in experimental sAD, support the potential use of MSC therapy for the treatment of neurodegenerative diseases.